The Packaging Development of Homkradung-nga rice Affecting the Commercial Response of Bor-Khor’s Housewife’s Group in Takbai District, Narathiwat Province - ประดิษฐ์ เกศแก้ว (Princess of Naradhiwas University Journal, 2018)
The aims of this study were to 1) design and develop the packaging of Homkradung-nga rice for Bor-Khor’s Housewife’s Group in Takbai District, Narathiwat Province, and 2) to compare the commercial response of the original packaging and developed packaging. The study was divided into 3 phases which are Phase 1: investigating the information of the packaging: The interview form was used for 20 members of the Housewife’s Group and 3 government personnel. The interview investigated the information about the packaging, brand logo and product details displayed on the label. The questionnaire was used for 200 consumers to study information on the original packaging. Phase 2: designing and developing the packaging:The researcher created 5 prototype packages. The satisfaction on the prototype packages were evaluated by 408 samples consisted of Housewife Group’s members, consumers and government personnel. The samples were selected by purposive sampling method. Phase 3: comparing the commercial response to the original packaging and developed packaging determined by the percentage of the sales. The data was analyzed by calculating mean and percentage. The study suggests that the packaging that makes the product and brand stand out is using 110-microns vacuum bag (without text on it). The size of the bag is 20 centimeters wide and 28 centimeters long. The packaging contains one kilogram of rice. The bag is packed in a paper box that can hold 1 kilogram. The size of the box is 21 centimeters wide and 29 centimeters long. The color of the box is pink which represents women. The colors of the letters printed on the box are brown and golden yellow. The average of consumers’ satisfaction with the developed packaging in terms of the identity of the packaging is a high level ( = 4.14, S.D. = 0.54). The average of the graphic design is a high level ( = 4.11, S.D. = 0.49).The average of the structure of the packaging is a high level ( = 4.06, S.D. = 0.63). The commercial response towards the developed package is 26.99% higher than the original packaging.